2013
DOI: 10.1186/ar4217
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between angiogenic factors and capillaroscopic patterns in systemic sclerosis

Abstract: IntroductionWe sought to assess whether nailfold videocapillaroscopy (NVC) patterns are associated with levels of angiogenic factors in systemic sclerosis (SSc).MethodsCirculating endothelial progenitor cells (EPCs) and circulating endothelial cells (CECs) were measured in the peripheral blood of 60 consecutive SSc patients. Serum levels of eight endothelial markers were measured first in these 60 patients, and then in an independent replication cohort of 43 SSc patients in case of association with NVC pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 36 publications
3
42
0
3
Order By: Relevance
“…In SSc patients, the typical SD pattern, which is characterized by the presence of enlarged capillaries, capillary loss and distortion of the capillary array (De Angelis et al, 2009), might be related to impaired vasculogenesis. Interestingly, as observed recently in another study (Avouac et al, 2013), we observed decreased levels of EPCs in patients who presented with the late SD pattern on NFC. Indeed, the late SD pattern is characterized by severe capillary loss and disorganization of the capillary array (Cutolo et al, 2004) and might be associated with a decrease in EPC count.…”
Section: Discussionsupporting
confidence: 77%
“…In SSc patients, the typical SD pattern, which is characterized by the presence of enlarged capillaries, capillary loss and distortion of the capillary array (De Angelis et al, 2009), might be related to impaired vasculogenesis. Interestingly, as observed recently in another study (Avouac et al, 2013), we observed decreased levels of EPCs in patients who presented with the late SD pattern on NFC. Indeed, the late SD pattern is characterized by severe capillary loss and disorganization of the capillary array (Cutolo et al, 2004) and might be associated with a decrease in EPC count.…”
Section: Discussionsupporting
confidence: 77%
“…Taken together, these observations support the idea that an increase in the number and size of CT may be an aberrant attempt at vascular recovery in response to insufficient blood flow, to increase blood perfusion and oxygen supply to hypoxic tissues. Increased vascular endothelial growth factor (VEGF) levels have been reported in patients with the late NVC pattern and particularly with neoangiogenesis (13). Indeed, a chronic and uncontrolled overexpression of VEGF has been implicated in the altered and anarchic vessel morphology that characterizes neoangiogenesis and thus, VEGF overexpression may also drive the formation of profuse and pseudotumoral CT.…”
Section: Discussionmentioning
confidence: 99%
“…In that case, patients with absent or minor to moderate CT were merged together and further compared with patients with profuse CT. Patients with early and active NVC pattern were merged together and further compared with patients with the late NVC pattern, as previously reported (13). Analysis of variance was used to test the difference between the means of several subgroups of a variable.…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…For example, vascular endothelial growth factor (VEGF) is increased in angiogenesis in RA by high-mobility group box protein 1 (HMGB1) (52), also seen in other disease developments such as in systemic sclerosis (53), where microvascular damage and dysfunction represent the earliest morphological and functional markers (54).…”
Section: Discussionmentioning
confidence: 99%